2019
DOI: 10.3389/fpls.2019.01182
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Effectors From Uromyces appendiculatus, the Causal Agent of Rust on Common Bean, Can Be Discriminated Based on Suppression of Immune Responses

Abstract: Rust fungi are devastating pathogens for several important crop plants. The biotrophic lifestyle of rust fungi requires that they influence their host plants to create a favorable environment for growth and reproduction. Rust fungi secrete a variety of effector proteins that manipulate host target proteins to alter plant metabolism and suppress defense responses. Because of the obligate biotrophic lifestyle of rust fungi, direct evidence for effector function is difficult to obtain, and so suites of experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…In this study, maize secretome was found to be reduced by 36% upon colonization with T. virens (Nogueira-Lopez et al, 2018). Seven secreted Uaca_Ns effectors from the bean rust pathogen Uromyces appendiculatus were shown to suppress plant host innate immunity, by either dampening pathgogen-triggered immunity or preventing hypersensitive response (Qi et al, 2019).…”
Section: At the Frontline: Plant And Fungal Secretomes Mergementioning
confidence: 77%
“…In this study, maize secretome was found to be reduced by 36% upon colonization with T. virens (Nogueira-Lopez et al, 2018). Seven secreted Uaca_Ns effectors from the bean rust pathogen Uromyces appendiculatus were shown to suppress plant host innate immunity, by either dampening pathgogen-triggered immunity or preventing hypersensitive response (Qi et al, 2019).…”
Section: At the Frontline: Plant And Fungal Secretomes Mergementioning
confidence: 77%
“…We recently published a study identifying candidate effectors in U . appendiculatus [ 4 ]. Part of that study was to establish the expression patterns of these genes.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of 23 CEPs was confirmed using qRT-PCR assay in planta ( Figure 6). A previous study revealed that the C-terminus is important for recognition with host transcription factors [37,63]. As a result, we used N-terminal fusion based on the rationale that tags are removed from the signal peptide.…”
Section: Discussionmentioning
confidence: 99%
“…The seamless cloning primers are shown in Table S3. The successfully constructed subcellular localization vector was introduced into agrobacterium tumefaciens GV3101 using the liquid nitrogen quick-freezing method [37]. pBin-eGFP was unloaded into agrobacterium tumefaciens as a negative control.…”
Section: Cloning and Subcellular Localization Of Candidate Effectorsmentioning
confidence: 99%